1991
DOI: 10.1111/j.1365-3180.1991.tb01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of competition between wild oats (Avena fatua L.) and winter cereals

Abstract: Summary: This study examined the effects of competition on the growth of Avena fatua, winter wheat and winter barley. Plants were sampled at frequent intervals from replacement series experiments at two contrasting sites in the U.K. A. fatua was much slower to establish than the two cereals, but thereafter exhibited a faster rate of growth. In monoculture, it took a considerable time for A. fatua to reach a size equal to that of the cereals, but by the end of the experiments it was the largest of the three spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 19 publications
4
38
0
Order By: Relevance
“…Relative time of emergence has been identified as an important factor in crop-weed competition (O'Donovan et al 1985) and in legume-cereal intercrops (Tofinga et al 1993). Cousens et al (1991) concluded that the relative timing of morphological development is critical to the outcome of competition.…”
Section: Discussion Competitive Effects Of Oat Plants On Berseem Clovermentioning
confidence: 99%
“…Relative time of emergence has been identified as an important factor in crop-weed competition (O'Donovan et al 1985) and in legume-cereal intercrops (Tofinga et al 1993). Cousens et al (1991) concluded that the relative timing of morphological development is critical to the outcome of competition.…”
Section: Discussion Competitive Effects Of Oat Plants On Berseem Clovermentioning
confidence: 99%
“…This could be due to higher competitiveness of hybrids against weeds, development of fast and early canopy coverage with higher leaf area index values; higher root growth and crop dry weight (data not shown here). The competitive ability of crops against weeds mainly determine by higher plant height and dry matter accumulation, early canopy closure, enhanced leaf area leading to more light interception and shading over understory plant species, increased nutrient uptake, proliferate root growth, and allelopathic effects (Pavlychenko and Harrington, 1934;Balyan et al, 1991;Cousens et al, 1991;Cudney et al, 1991;Anwar et al, 2010;Bajwa et al, 2017). Early-ripening of improved rice cultivars and hybrids have the ability to acquire larger canopy coverage within a short period of time and can suppress the weed growth to a greater magnitude over traditional, open-pollinated, long-duration cultivars (Zhao, 2006;ICAR, 2007;Sardana et al, 2017;.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, community dominance (as determined by relative DM production) at the first harvest was with the crop, likely due to the competitiveness of the prostrate winter triticale vs. wild oats. After the first harvest, however, community dominance shifted to the weed, possibly because wild oat (which was the dominant weed) had a higher net assimilation rate than the crop (Cousens et al 1991). Finally, the dominance shifted back to the crop.…”
Section: Dry Matter Productionmentioning
confidence: 99%
“…Thurston (1962) attributed effective suppression of wild oat by winter wheat (Triticum aestivum L.), winter rye (Secale cereale L.) and winter barley (Hordeum vulgare L.) silage crops to their presence in spring when wild oat was germinating. Although wild oat seedling mass remained initially smaller than the crop seedling mass, wild oat can grow faster than either winter wheat or barley (Thurston 1962), because of its higher net assimilation rate (Cousens et al 1991). Since winter rye residues are phytotoxic to some weeds (Weston 1996), allelopathy may also have played a role in the Thurston studies.…”
mentioning
confidence: 99%